Amino Acid‐Derived Phosphonium Salts‐Catalyzed Michael Addition of 3‐Substituted Oxindoles. Issue 13 (5th September 2013) - Wu, Xiaoyu; Liu, Qin; Liu, Yong; Wang, Qun; Zhang, Ying; Chen, Jie; Cao, Weiguo; Zhao, Gang
Abstract A new type of phosphonium phase‐transfer catalyst prepared from easily available chiral amino acids was evaluated in a model reaction between oxindole and methyl vinyl ketone, and the catalyst derived from isoleucine was found to be the best. Michael additions of 3‐monosubstituted oxindoles to methyl vinyl ketone, acrolein or propargyl aldehyde proceeded smoothly to afford 3, 3‐disubstituted oxindoles in good to excellent yields with moderate to excellent ees. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>